(3GdEaGOI hGdGYJHGQ aj GdCehQ GdeTGgOI hGdMhGOK GdeYGjfI HCQV eUQs - (3YHO GddWja Hf jhSa Hf eMeO Hf Ydj GdHZOGOj, ehab GdOjf, hjYQa HGHf GddHGO, hHGHf fbWI,J (B629 (3g` s ((3HjQhJ GdbGgQI s)
(3ChdgG (B:s
(3hHYO aEfj deG GfgjJ cJGHj aj CNHGQ eUQ GdeTJed Ydi KdGKI YTQ aUdG QCjJ Cf CaQO efg GdMhGOK GdMGVQI hGdBKGQ GdHGOjI GdeTGgOI s
(3BNQgG (B:s
(3agPG eG bUOJ EbJUGUg aj CMhGd gPg GdcGFfI adjcf efJgi GdebGdI hBNQ GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B342 - (3U(B409s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B61 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B15s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B481 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B881 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B41 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs